Riscoprire la storia per orientarsi nel presente. Qualche nota su critica e totalità - Bisardi, Antonella (L'ospite ingrato, 2021)
This paper, being part of a debate on the role of the concepts of totality and dialectics in today’s society, proposes a positive evaluation of them, claiming their urgency. The reason is found in the spreading of postmodern logic and in the consequent alienation of individuals. Through partial reconstructions of some theoretical connections of Fredric Jameson, Antonio Gramsci, Mark Fisher and Roberto Finelli, the necessity of a deep thought that rejects the vacuous essentialism dominant today has been highlighted. The totalizing image of today’s capitalism risks to prevent a real awareness of the processual and dynamic character of history and to imprison us in an eternal present. The means through which it seems possible to rewrite a history erroneously proposed as immutable is undoubtedly education, the engine of acquisition of a critical consciousness.